Evaluation of an integrated stepwise rehabilitation model following Nuss procedure in pediatric patients - Li, Wen-Jing; Cao, Li-Li; Li, Chan; Yang, Jing-Jing; Wang, Hui; Tong, Yao (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the application and rehabilitation outcomes of an integrated stepwise rehabilitation training model in pediatric patients undergoing minimally invasive repair of pectus excavatum (Nuss procedure).MethodsA cohort of 97 children who underwent the Nuss procedure between July 2019 and August 2021 were included in the study. Participants were divided into an observation group (n = 52) and a control group (n = 45). The observation group received a stepwise rehabilitation training model in addition to standard perioperative care, while the control group received only routine care. Rehabilitation outcomes, including physical development, pulmonary function, self-care ability, and treatment satisfaction, were assessed over a 12-month period.ResultsThere were no statistically significant differences in baseline characteristics or postoperative complications between the two groups. In the observation group, all pulmonary function parameters demonstrated significant improvements at both 6- and 12-months post-surgery (p < 0.001). The control group did not indicate significant changes at 6 months, with improvements noted only at 12 months (p < 0.001). Postoperative satisfaction and self-care ability in the control group improved significantly at the 12-month follow-up. In contrast, the observation group exhibited significant improvements in these parameters as early as 6 months postoperatively.ConclusionEarly implementation of an integrated stepwise rehabilitation training model enhances the recovery process in pediatric patients following the Nuss procedure. This approach is both effective and economically feasible, providing a practical framework for post-surgical rehabilitation.